Hemp There it Is: Examining Consumers’ Attitudes Toward the Revitalization of Hemp as an Agricultural Commodity - Shelli Rampold; Zachary Brym; Michaela S Kandzer; Lauri M Baker (Journal of Applied Communications, 2021)
This study was conducted to examine Florida consumers’ stance on legalizing the growing and processing of hemp, recently redefined as an agricultural commodity. Factors were explored that may explain their stance to provide insight into the communication needs in the early stages of the U.S. hemp industry revival. Results indicated that respondents who had more favorable attitudes toward legalizing hemp were also more likely to fall within the category of being overall “for legalizing hemp” when offered a binary choice. Further, attitude toward legalizing hemp was predicted by respondents’ objective knowledge of hemp topics, attitude toward legalizing marijuana, and perceived personal relevance of legalized hemp cultivation and production. A strong association between hemp and marijuana was also observed in both the quantitative and qualitative findings, and respondents indicated some confusion regarding the mind-altering properties of marijuana compared to hemp. As such, a key recommendation is that early communication messages and strategies be tailored toward educating the public on differences in the uses and psychoactive properties of hemp and marijuana. Future research is needed to identify other key messages needed to enhance public understanding of hemp, as well as the best methods of delivering such. Future research should be conducted with other hemp stakeholders, including policymakers, hemp license-holders, and other farmers and industry members to reconcile potential differences in key stakeholder perceptions and enhance the future viability of the industrial hemp market.
Keywords: hemp; consumer buy-in; agriculture; marijuana; legalization